Glyphosate-resistant Italian ryegrass (Lolium perenne ssp. multiflorum) control with preemergence and postemergence herbicide programs. (24th February 2022) - Bond, Jason A.; Allen, Tom W.; Seale, John W.; Edwards, Henry M.
Abstract: A field study was conducted twice in Elizabeth, MS, at on-farm sites in 2010–11 and 2011–12, and twice in 2012–13 at Mississippi State University's Delta Research and Extension Center in Stoneville, MS, to evaluate glyphosate-resistant (GR) Italian ryegrass control and crop response to fall treatments followed by postemergence herbicide treatments in winter and/or spring. Italian ryegrass was controlled ≥92% and 61% following S -metolachlor and tillage 77 d after fall treatments (DA-FT), respectively. S -metolachlor fall treatment provided 33% greater control than clethodim winter treatment at 21 d after winter treatments (DA-WT). Tillage fall treatment followed by (fb) clethodim winter treatment fb paraquat spring treatment provided similar control (93%) to treatments containing S -metolachlor fall treatment fb a winter or spring herbicide treatment (≥93%) 24 d after spring treatments (DA-ST). Greatest soybean and corn density and yield were also observed following programs containing S -metolachlor fall treatment. Sequential postemergence herbicide treatments were not required to increase corn and soybean density and yield when S -metolachlor was used as a fall treatment. Growers have the best opportunity to maximize GR Italian ryegrass control when S -metolachlor fb a winter or spring herbicide treatment is used.